Labor market reintegration strategies of Albanian return migrants from Greece - Armela Xhaho; Ajay Bailey; Erka Çaro (Discover Global Society)
Abstract For many migrants, returning to their country of origin is an important turning point in their migration trajectory. However, whether reverse migration proves successful depends largely on whether returnees are again able to participate in the social, economic, cultural, and political life of their country of origin. This paper draws on 37 biographical interviews conducted with Albanian returnees in three different geographical areas of Albania: Fier, Tirana, and Voskopoja. It aims to capture the diverse strategies the return migrants employed in navigating the labor market upon their return. We examine how the social and human capital the returnees accumulated while abroad shaped their patterns of reintegration into the labor market. We find that the returnees’ social capital in the form of social relationships and their human capital in the form of work experience influenced their entrepreneurial activities in their home country. Moreover, we observe that some of the returnees who were able to capitalize on their migration experiences in their host country introduced a new work culture and new products to their home country and offered better quality work than their local competitors. Our findings further indicate that while the returnees’ social networks improved their economic prospects, the levels of trust and social responsibility in these networks enabled them to develop and expand their business activities.